The Urgency of Indonesian Notary Association (INI) in Development And Supervision of Notary - Elok Sunaringtyas Mahanani; Iswi Hariyani (Jurnal Ilmu Kenotariatan, 2023)
Notary is a job or position that requires ethics in carrying out its authority. The code of ethics is used as a guideline for member behavior, accompanied by clear and strict sanctions for violators of the code of ethics. The notary's code of ethics aims to ensure that the notary profession operates professionally with motivation and orientation towards intellectual abilities and opinions rationally and critically and upholding moral values. This article's research type is normative juridical, with a statutory regulatory approach and a conceptual approach. Discussions on enforcement and supervision of the implementation of the Notary's professional code of ethics are carried out through the Notary's Honorary Council. Notaries feel the need for supervision to prevent possible irregularities in carrying out their positions which are not in accordance with the legal corridors and professional code of ethics as well as abuse of authority or trust given to Notaries. Conclusion Based on the description above, it can be concluded that the urgency of the Indonesian Notary Association in providing guidance and supervision aims to prevent its members from committing acts that violate the law. commit violations and comply with existing codes of ethics as an effort to maintain their honor and dignity as public officials. So the efforts carried out by INI are in several steps, namely: Guidance by related agencies, coordination and cooperation between Notaries and INI, and ongoing supervision. Law enforcement efforts are not only carried out by INI alone, but Notaries need to pay attention to what is called professional behavior which has the following elements: Have strong moral integrity, must be honest with clients and themselves (intellectual honesty), be alert regarding the limits of their authority, not solely based on monetary considerations. KEYWORDS: Urgency, Notary Association, Guidance and Supervision